Analysis and interpretation of mixture DNA using AS‐PCR of mtDNA. Issue 11 (25th February 2019) - Xu, Feng‐ling; Ding, Mei; Xia, Xi; Wu, Xue; Zhang, Jing‐jing; Xing, Jia‐xin; Xuan, Jin‐feng; Yao, Jun; Wang, Bao‐jie
Abstract: Semi‐nested PCR with allele‐specific (AS) primers and sequencing of mitochondrial DNA (mtDNA) were performed to analyze and interpret DNA mixtures, especially when biological materials were degraded or contained a limited amount of DNA. SNP‐STR markers were available to identify the minor DNA component using AS‐PCR; moreover, SNPs in mtDNA could be used when the degraded or limited amounts of DNA mixtures were not successful with SNP‐STR markers. Five pairs of allele‐specific primers were designed based on three SNPs (G15043A, T16362C, and T16519C). The sequence of mtDNA control region of minor components was obtained using AS‐PCR and sequencing. Sequences of the amplification fragments were aligned and compared with the sequences of known suspects or databases. When this assay was used with the T16362C and T16519C SNPs, we found it to be highly sensitive for detecting small amounts of DNA (∼30 pg) and analyzing DNA mixtures of two contributors, even at an approximately 1‰ ratio of minor and major components. An exception was tests based on the SNP G15043A, which required approximately 300 pg of a 1% DNA mixture. In simulated three contributor DNA mixtures (at rate of 1:1:1), control region fragments from each contributor were detected and interpreted. AS‐PCR combined with semi‐nested PCR was successfully used to identify the mtDNA control region of each contributor, providing biological evidence for excluding suspects in forensic cases, especially when biological materials were degraded or had a limited amount of DNA.